The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.molcatb.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme A-free activity, crystal structure, and rational engineering of a promiscuous β-ketoacyl thiolase from Ralstonia eutropha

Abstract: Thiolases catalyze the formation of carbon-carbon bonds in diverse biosynthetic pathways. The promiscuous β-ketoacyl thiolase B of Ralstonia eutropha (ReBktB) has been utilized in the in vivo conversion of Coenzyme A (CoA)-linked precursors such as acetyl-CoA and glycolyl-CoA into β-hydroxy acids, including the pharmaceutically-important 3,4-dihydroxybutyric acid. Such thiolases could serve as powerful carbon-carbon bond-forming biocatalysts in vitro if handles less costly than CoA were employable. Here, thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…The different Lα1 helix lengths are also thought to play a role in the selectivity of BktB, a T1-like bacterial enzyme. 29 On the basis of the sequence variability of the Lα1 region, the size of the Lα1 helix is difficult to determine by sequence alignment and appears to be the same length in T1, T2, and CT-like thiolases. The ability to carry out structure-guided alignment thus helps to clarify its role in longchain permissiveness (Figure S3).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The different Lα1 helix lengths are also thought to play a role in the selectivity of BktB, a T1-like bacterial enzyme. 29 On the basis of the sequence variability of the Lα1 region, the size of the Lα1 helix is difficult to determine by sequence alignment and appears to be the same length in T1, T2, and CT-like thiolases. The ability to carry out structure-guided alignment thus helps to clarify its role in longchain permissiveness (Figure S3).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Although BktB only exhibits 51% sequence identity with PhbA, the active site is highly similar, with 86% of the residues within 10 Å of the PhbA acetyl-CoA carbonyl center conserved between PhbA and BktB (Supplementary Table I). Two unliganded crystal structures were available for BktB (Kim et al, 2014; Fage et al, 2015), and due to the active-site similarity, the Z. ramigera PhbA structures,1M3Z and 1DM3 were used as templates to build structures of BktB with acetyl-CoA and butyryl-CoA bound.…”
Section: Resultsmentioning
confidence: 99%
“…The first attempt at thiolase engineering described in the literature used directed evolution to arrive at a variant that exhibited robust acetoacetyl-CoA product formation and lower sensitivity to inhibition by CoASH (Mann and Lütke-Eversloh, 2012). Another effort to engineer the thiolase to accommodate α-substituted acyl-CoAs relied on intuition guided rational mutagenesis of just one residue in close proximity of the active site but employed coenzyme-A analogs (Fage et al, 2015). During the preparation of this manuscript, two additional studies were published which reported rational mutagenesis of S. cerevisiae Erg10 thiolase and two A. suum thiolases for increased selectivities towards α-substituted substrates (Torras-Salas et al, 2018 and Blaisse et al, 2018 respectively).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Our previous studies established that BktB operates on acyl-SNAC substrates, but how active and stereocontrolled PhaB would be toward a truncated acyl thio-ester was unknown. 13 An acetyl-CoA synthetase (ACS, Streptomyces coelicolor ) that can ligate acetate with diverse thiol acceptors, and a glucose dehydrogenase (GDH, Bacillus subtilis ) that oxidizes D -glucose to regenerate NADPH from NADP + were also employed. 7…”
mentioning
confidence: 99%
“…However, the M290A point mutant of BktB mutant catalyzes the thiolysis of α-alkyl-β-ketoacyl NAC thioesters and could possess the desired biosynthetic activity. 13 Other thiolases ( e.g ., Erg10 from Saccharomyces cerevisiae ) are also being engineered to generate α-substituted β-ketoacyl thioesters. 18…”
mentioning
confidence: 99%